2009 IEEE International Conference on Robotics and Automation 2009
DOI: 10.1109/robot.2009.5152429
|View full text |Cite
|
Sign up to set email alerts
|

Combining color-based invariant gradient detector with HoG descriptors for robust image detection in scenes under cast shadows

Abstract: In this work we present a robust detection method in outdoor scenes under cast shadows using color based invariant gradients in combination with HoG local features. The method achieves good detection rates in urban scene classification and person detection outperforming traditional methods based on intensity gradient detectors which are sensible to illumination variations but not to cast shadows. The method uses color based invariant gradients that emphasize material changes and extract relevant and invariant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In this sense, Gevers and Smeulders [47] and later Villamizar et al [42], deeply analysed diverse colour models by evaluating their robustness for object recognition under different image parameters. This comparison, summarized in Table I, concluded that the colour model to be chosen depends on the imaging conditions.…”
Section: A Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Gevers and Smeulders [47] and later Villamizar et al [42], deeply analysed diverse colour models by evaluating their robustness for object recognition under different image parameters. This comparison, summarized in Table I, concluded that the colour model to be chosen depends on the imaging conditions.…”
Section: A Feature Extractionmentioning
confidence: 99%
“…In this way, colour-based invariant gradients have been combined with Histogram of Oriented Gradient (HoG) local features [42] for object detection in outdoor scenes (such as urban scenes) under cast shadows. The approach is, however, limited by the constrained nature of the environments.…”
Section: Introductionmentioning
confidence: 99%
“…Bag of Words (BoW) model [13,14,15,16,17] is originated from natural language processing tasks and information retrieval. For image analysis, a visual analogue of a word is used in the BoW model, which is based on the vector quantization process by clustering low-level visual features of local regions or points, such as color, texture, and so forth [18].…”
Section: Bag Of Featuresmentioning
confidence: 99%
“…SIFT and SURF can be used in image categorization. Generally, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] better performance and efficiency of training and classification depend on better representation and clustering of features.…”
Section: Introductionmentioning
confidence: 99%
“…The best performing methods often use a monolithic representation of people, such as a HOG descriptor [9], and discriminative classifiers. Models of this type have recently been extended to incorporate motion [10], [36] and color [35] features. They have also been applied to upper body detection [18], and have been integrated within larger systems to enable obstacle detection in mobile environments [14].…”
Section: Introduction and Related Workmentioning
confidence: 99%